The Bodily Nature of Consciousness : Sartre and Contemporary Philosophy of Mind - Wider, Kathleen Virginia, 1944- (Book collections on Project MUSE., 1997)
In this work, Kathleen V. Wider discusses Jean-Paul Sartre's analysis of consciousness in Being and Nothingness in light of recent work by analytic philosophers, psychologists, and neuroscientists. She brings together phenomenological and scientific understandings of the nature of consciousness and argues that the two approaches can strengthen and support each other. Work on consciousness from two very different philosophical traditions - the continental and the analytic - contributes to her explanation of the deep-seated intuition that all consciousness is self-consciousness.